Benevolent sexism toward men: Its social legitimation and preference for male candidates. (July 2014) - Russo, Silvia; Rutto, Filippo; Mosso, Cristina
The present research investigated the relationship between system justification beliefs and the endorsement of ambivalent sexist attitudes toward men. In Study 1 (web-based questionnaire, N = 220) we explored the relationship between system justification (SJ), and hostile and benevolent attitudes toward men (HM and BM). Results showed that SJ was positively related to BM but not to HM. In Study 2 (paper-and-pencil questionnaire, N = 158), we tested the mediating role played by BM and HM in the relationship between SJ and the preference for male candidates. We replicated Study 1 results and showed that BM, but not HM, was positively related to the dependent variable; moreover SJ exerted an indirect and positive effect on the preference for male candidates as mediated by BM. Finally, supplementary analyses showed that the relationship between SJ and BM was positive and significant for women only. Results are discussed in light of system justification theory and of BM as an additional form of legitimization and maintenance of the status quo.